Identification of Zakat Impact Measurement Tools - Bahri, Efri Syamsul; Sulistiawati, Sulistiawati (AKTSAR: Jurnal Akuntansi Syariah, 2021)
Zakat management aims to alleviate poverty and improve the welfare of mustahiq. Various instruments for measuring the impact of zakat on mustahiq are needed to measure the achievement of the goals of zakat management. This study aimed to identify and analyze several instruments to measure the impact of zakat. The analysis was conducted by conducting a literature study on various reference sources. The analysis used a descriptive analysis approach and a content analysis approach. The results of this study found four instruments for measuring the impact of zakat: Social Return on Investment (SROI), Center of Islamic Business and Economic Studies (CIBEST), Sustainable Livelihood Impact Assessment (SLIA), and BAZNAS Index for Sustainable Water and Sanitation (BI- WAS). Overall, all instruments can measure the impact of zakat on mustahiq for zakat disbursements to mustahiq